Konsumsi lemak total, lemak jenuh, dan kolesterol sebagai faktor risiko sindroma metabolik pada masyarakat perkotaan di Denpasar - Ni Komang Wiardani; Pande Putu Sri Sugiani; Ni Made Yuni Gumala (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Metabolic syndrome is a health problem with its prevalence increasing in the worldwide. It is characterized by a group metabolic factor including abdominal obesity, dyslipidemia, elevated blood pressure and insulin resistance. Metabolic syndrome affected by changes in lifestyle and unhealthy dietary patterns with high cholesterol, saturated fatty acid and trans fatty acid.Objective: The study conducted to know relationship between fat consumption with metabolic syndrome among adult people in Denpasar city.Method: The case control study designed was applied. The cases were adult people who had metabolic syndrome, and the control was healthy people from the case-neighboring household. Total subject were 130, taken by consecutive sampling: 65 cases and 65 controls. The subject identity, fat intake, waist circumference, blood pressure and fasting blood sugar were collected. The food frequency questionnaire (FFQ) was used to measure fat consumption and blood glucose test meter for measuring fasting blood sugar. Mantel Haenzel statistic analysis were used to test the association of fat intake with metabolic syndrome.Result: The study showed that means of syndrome metabolic component in case higher than control (p<0.05). Waist circumference in case was 97.23 cm, blood pressure was 141.4/93.3 mmHg, fasting blood glucose was 132 mg/dl. There were significant difference between intake fat total, cholesterol, saturated fatty acid (SAFA) and frequency of intake in case and control (p<0.05). Intake fat on cases were fat total 85.5% >25% energy total/day, SAFA 90.8% >10%, cholesterol 55.4% >300 mg/day. Odd Ratio Mantel Haenzel analysis showed that fat consumption (fat total, cholesterol and frequency consumption of fat were risk factor to metabolic syndrome (OR >1)).Conclusion: There was significant relations between fat consumption (fat total cholesterol, SAFA, frequency of fat consumption) with metabolic syndrome among adult people for Denpasar City.